Current trends in compounding of medicines and its legislative regulation in foreign countries - L. P. Savchenko; V. A. Georgiyants (The State Expert Center of the Ministry of Health of Ukraine, 2020)
Compounding medicines preparation is part of the proper pharmaceutical supply of the population. Unfortunately, its volumes in Ukraine have been declining recently, but the spread of medicines production in privately owned pharmacies indicates the prospects of this activity type. The aim of the work was the analysis of the current state of medicines compounding and its legislative regulation in foreign countries, formulation of the main directions of the Ukrainian legislation reforming on this issue. The materials of the research were scientific publications in peer-reviewed foreign journals with using bibliosemantic method, the method of generalization and systematic data analysis. The analysis of publications concerning the practice of medicines preparation in foreign countries showed its volume increasing. In most countries, such activities are an integral part of pharmaceutical care and the provision of medicines to the population. Along with conventional pharmacies, the widespread medicines compounding in hospital pharmacies. The structure of drug production differs in each country. According to the Global Market Insights report for 2018, the main therapeutic areas in the structure of compounding medicines market were hormone replacement therapy, analgesia, dermatology, specialized drugs and parenteral nutrition. The regulatory framework governing the medicines compounding was reviewed in the last few years. The EU updated the PIC/S Guide and approved the second version of the EU Council Resolution on the medicines compounding. To control the spread of sterile medicines serial preparation in the United States since 2013 this activity is controlled by the FDA. Compliance with GMP requirements is a mandatory requirement for the serial preparation of sterile medicines abroad. Thus, the development of medicines compounding is a promising area of pharmaceutical activity. Despite the reduction in the number of compounding pharmacies, Ukrainian pharmacies are also involved in the preparation of specific medicines. A number of regulatory documents, the requirements of which are similar to international ones, regulates the quality control of compounding medicines. However, to comply with modern world trends, it is necessary to review and update this legislation.